Litopenaeus vannamei : Feeding and Nutritional Needs - Adam Setiawan (Academic Letters, 2025)
Feed management is one of the keys to success in the process of vannamei shrimp (Litopenaeus vannamei) cultivation. Good feed is feed that contains complete nutrition. Good feed is feed that contains complete nutrition, is not damaged and is not moldy. The nutrients needed by vannamei shrimp include protein, fat, carbohydrates, vitamins, minerals and essential amino acids. These nutrients are used for shrimp growth and reproduction activities. In general, this article explains the provision of feed and nutrition needed for vannamei shrimp to grow well.